2014
DOI: 10.2478/bvip-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of galanin and galanin receptors in the wall of the colon in pigs experimentally infected with Brachyspira hyodysenteriae

Abstract: The expression of galanin (GAL) and its three receptors (GalR1, GalR2, and GalR3) were studied with real-time PCR in the colonic wall of pigs suffering from experimental colitis caused by the infection with Brachyspira hyodysenteriae. The expression was studied in the muscular membrane, mucosa/submucosa layer, and in lymphocytes isolated from mucosa/submucosa. The expression levels were normalized to glyceraldehyde-6-phosphate dehydrogenase (GAPDH) expression and compared to expression levels in control animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…48 This study has revealed that only in the stomach tissues directly adjacent to the ulcer, thus affected by acute inflammatory process, the expression of both subtypes of galanin receptors was increased. However, previous studies have demonstrated that in the porcine pylorus 25 and in the colon 36 their expressions were not significantly changed and even distinctly decreased, respectively. Although, as mentioned before, in the latter study the tissue degradation might have affected the results, all these variations between different parts of the por- Although the functional significance of data gained from the present experiment have to be further verified by other scientific disciplines, based on the literature review it is tempting to speculate that galanin is strongly involved in protective and recovery processes, transduction of pain and, partially, in the modulation of the peristalsis in the (porcine) stomach.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…48 This study has revealed that only in the stomach tissues directly adjacent to the ulcer, thus affected by acute inflammatory process, the expression of both subtypes of galanin receptors was increased. However, previous studies have demonstrated that in the porcine pylorus 25 and in the colon 36 their expressions were not significantly changed and even distinctly decreased, respectively. Although, as mentioned before, in the latter study the tissue degradation might have affected the results, all these variations between different parts of the por- Although the functional significance of data gained from the present experiment have to be further verified by other scientific disciplines, based on the literature review it is tempting to speculate that galanin is strongly involved in protective and recovery processes, transduction of pain and, partially, in the modulation of the peristalsis in the (porcine) stomach.…”
Section: Discussionmentioning
confidence: 76%
“…This study has revealed that only in the stomach tissues directly adjacent to the ulcer, thus affected by acute inflammatory process, the expression of both subtypes of galanin receptors was increased. However, previous studies have demonstrated that in the porcine pylorus and in the colon their expressions were not significantly changed and even distinctly decreased, respectively. Although, as mentioned before, in the latter study the tissue degradation might have affected the results, all these variations between different parts of the porcine gastrointestinal tract indicate a unique role played by each receptor in response of individual tissues to the pathology.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Then, from each cDNA sample Real-Time PCRs were performed for the following genes: Gal, GalR1, GalR2, GalR3 and porcine glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as the housekeeping gene, each in triplicate. The primers were designed with Primer-BLAST software ( http://ncbi.nlm.nih.gov ) and their detailed descriptions are enclosed in our previous study [ 37 ]. Sequences of primers are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%